Soil health – climate - agriculture nexus - African Union Development Agency (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This poster was presented at the Africa Fertilizer and Soil Health Summit 2024 side event on Leveraging Policy, Practice and Research for Monitoring Soil Health.